Initial Evidence for Understanding the Relationship between Product Line Architecture and Software Architecture Recovery - Lima Neto, Crescencio Rodrigues; Cardoso, Mateus Passos Soares; Chavez, Christina Von Flach Garcia; Almeida, Eduardo Santana De (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2015: Anais do IX Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2015)
Context: Over the years, the interest on software architecture recovery has increased. Due to software product line inherent complexity, the recovery of product line architecture is crucial to alleviate difficulties and enable benefits during the SPL development. Objective: In order to gather data and evidence about the relationship between product line architecture and software architecture recovery, (Method:) we performed a literature survey using some steps of systematic literature review method and an exploratory study. Results: We identified the appearance of more elaborated studies over the years and the majority of solution proposals are used to recover the architecture from legacy systems source code to provide the SPL reference architecture. Conclusion: Most of the studies presented solution proposal combined with case studies. But, only a few of them address empirical evaluation. With the software architecture recovery evolution, more research combining recovery of product line architecture and empirical evaluation still necessary.